Extraction force and its determinants for minimally invasive vertical tooth extraction. (May 2020) - Dietrich, Thomas; Schmid, Ivan; Locher, Michael; Addison, Owen
Abstract: Background: Minimally invasive vertical extraction devices have been developed to minimise the need for flap surgery and trauma to alveolar bone during tooth extraction. The objective of this study was to measure the forces required for vertical tooth extraction and evaluate the determinants of these forces. Methods: The investigators coupled a precision load cell with a Benex® extractor to record extraction forces for 59 consecutive routine extractions of tooth roots. Age, sex, tooth type, root surface attachment area (RSAA) and whether or not the tooth was in functional occlusion were evaluated as determinants of extraction forces using linear mixed models. Results: Maximum extraction forces (Fmax ) varied widely from 41N to 629N. On average, maximum extraction forces were 104N (95% CI: 38N, 169N) higher for teeth/roots in occlusion vs. teeth not in occlusion. An increase in RSSA by one standard deviation was associated with a marked increase in Fmax by 64N (95% CI: 34N, 94N). Extraction forces were not associated with age, sex or tooth type (maxillary vs. mandibular). Conclusions: Extraction forces using the Benex® vertical extraction system vary widely and can be less than 50N or exceed 600N. On average, higher extraction forces are required to extract teeth with longer and thicker roots, as well as for teeth that are in functional occlusion.